Os nomes e a nomeação de espaços acadêmicos: memória e ideologia na toponímia da Universidade Federal de Alagoas - Aragão, Rafaela Simias (2025)
This research analyzes the naming process of academic public spaces at the Federal University of Alagoas (UFAL) from the perspective of Critical Toponymy, investigating place names and naming processes as a reflection of institutional memory, academic identity, and power relations. We seek to answer the following question: How do appointment processes (or their absence) in the academic spaces of UFAL reflect institutional ideologies and practices, and how do they contribute to the construction of memory and identity of the academic community? The objectives of this study are to catalog and describe the names of the academic spaces of UFAL as an autonomous and sui generis locus; Analyze, from the perspective of Critical Toponymy, how the naming of the academic spaces of UFAL reflects elements of ideology, memory and identity of the academic community, evidencing processes of valuation and silencing of some narratives and Investigate the social and political and institutional implications of the appointment processes and the absence of names in academic spaces. Considering the role of denominational acts as instruments of institutional, ideological representation and construction of collective identity, took as theoretical foundation studies of Onomastics and Human and Cultural Geography that collaborate to the understanding of the phenomenon studied here, such as ideology, memory, and identity, as Alderman (2002), Berg e Vuolteenaho (2009) and Lima e Carvalhinhos (2023). The methodology adopts a qualitative-quantitative approach, combining documentary research, bibliographic, and on-site observation in all UFAL campuses - A. C. Simões, Arapiraca, CECA Delza Gitaí e Sertão. The data were collected, coded, and treated in analytical categories to understand patterns and trends in naming public academic spaces. The results indicate that the principal and oldest campus, A. C. Simões, preserves a consolidated institutional memory, often by paying homage to a twentieth-century Alagoas elite. The most recent campuses and units, founded in this century from the Reuni program, present significant naming standardization through memorable acronyms. On the other hand, the Campus of Sertão shows a specific local identity by expressing, in its toponymy, elements of belonging to the rural environment. The study, unprecedented in relation to the treatment of names of public academic environments, contributes to the debates on university identity, institutional memory and appointment policies by revealing how these processes reflect power and belonging relations in the Brazilian public university.